Prevalence of acute intestinal infections and their role in human pathology (review) - Kozishkurt, E. V. (Journal of Education, Health and Sport, 2019)
Acute intestinal infections (AII) are one of the most common infectious diseases, the eighth most important cause of annual mortality among all age groups, and the fifth most common cause of death among children under 5 years of age worldwide. From 3 to 5 million children are affected each year, with nearly 446.000 fatalities. This is facilitated by: international migration, the interstate exchange of food products and raw materials of animal origin, the intensification of industrial production of livestock and poultry products, urbanization, activation of recreational processes, climate change, environmental degradation. Viruses are the dominant etiological factors, both during the period of a seasonal increase in the incidence of AII (65-76% of cases) and according to the analysis of sporadic cases (62.6%). The most common and significant viral agents of the causative agent of AII rota-, calici, adeno- and astroviruses. In most acute respiratory infections, the immune response formed in childhood is sufficient protection against infection in more advanced adulthood. The main reason for the absence or insufficiency of immune defense is a significant genetic and antigenic diversity of viral pathogens. The only means of identifying viruses are molecular genetic methods. Currently, there are no effective measures to deal with outbreaks of AII. The quality of drinking water remains the most important way of their prevention, which is a very difficult task for many countries. The development of vaccines for most viral pathogens is difficult. One of the promising methods for preventing the incidence of AII is the use of boiled water and the development of food processing technologies with a high risk of virus contamination, which include seafood, fresh vegetables and ready-to-eat foods.